Revamping agricultural R&D - Pardey, Philip G.; Alston, Julian M. (International Food Policy Research Institute, 1995)
Agricultural research and development (R&D) is big business. Worldwide investments in public-sector agricultural R&D totaled about US$17 billion in 1990. But business as usual may not be sustainable. As governments trim budgets, public support for national and international research is coming under closer scrutiny. Budget makers are asking whether the current R&D institutions are still needed. Although the details of the debates concerning research policies differ from country to country, many of the fundamental questions about the public role in agricultural R&D are common to most countries. The financing, organization, and management of public-sector R&D will have to be dealt with in an integrated way. Although the details of the debates concerning research policies differ from country to country, many of the fundamental questions about the public role in agricultural R&D are common to most countries. The authors conclude that different research intensities will be appropriate for different research programs, in different places, and at different times, depending on the expected costs and benefits."